A performance cultural do Ticumbre Conceição da Barra - ES Brasil: identidade e ancestralidade - Freire Schiffler , Michele (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
This research examines the importance of oral literature in quilombola communities identity building from the North area of Espirito Santo State, known as “Sapê do Norte”. It is observed their singing, their plot, melody, tune, verbal and body performance which were recorded and transcribed from the regional festival “Baile de Congos de São Benedito”. The corpus shows a series of social tensions surrounding the region, which shows a strong relation between cultural heritage, ancestry, and territorial issues, as well as constant processes of dispossession and hybridism in the religious, social, and linguistic fields. The oral literature, effected through the cultural performance and the constant exchange performed with the audience accesses the tradition and ancestral wisdom in enunciative practice. Orality revives and refreshes the wisdom of the ancestors, while at the same time, engendered by this knowledge and diffusing the tradition of African origin.